Double benefit of metformin treatment: improved bladder function in cyclophosphamide-induced cystitis and enhanced cytotoxicity in cancer cells - (:unkn) unknown (SPRINGER, 2021)
Cyclophosphamide (CP) is a widely used anti-neoplastic drug; however, it leads to bladder dysfunction in the form of hemorrhagic cystitis that is a serious dose-limiting complication in cancer patients. We aimed to evaluate the protective effects of metformin (MET) in a mouse model of CP-related cystitis in parallel with its effect on CP-induced cytotoxicity in a breast cancer cell line, MDA-MB-231. Cystitis was induced by a single intraperitoneal injection of CP (300 mg/kg), and mice were administered MET, mesna, or vehicle treatment. 24 hours after cystitis induction, the bladders were removed for histopathological analysis and ex vivo evaluation of detrusor muscle contractility. The effect of MET on the cytotoxicity of CP in MDA-MB-231 cells was evaluated as the viability of the cells via MTT assay. Histopathological evaluation confirmed that CP induced a severe cystitis, and MET partially inhibited CP-induced bladder damage. Carbachol-evoked cholinergic contractions were significantly decreased in detrusor strips of mice injected with CP only compared to control (E-max=293.67 +/- 20.00 vs. 497.79 +/- 21.78 mg tension/mg tissue, respectively). In CP-injected mice, treatment with 100 mg/kg MET restored cholinergic contractions (E-max=473.72 +/- 62.61 mg tension/mg tissue). In MDA-MB-231 cells, MET decreased their viability, and the combination of MET and CP caused more decrease in cell viability as compared to CP alone (p<0.05), demonstrating that MET enhances the cytotoxicity of CP in these cancer cells. Our results indicate that MET has a strong potential as a therapeutic adjuvant to prevent CP-induced cystitis while enhancing the efficacy of CP.
Keywords: Bladder dysfunction; Cyclophosphamide; Cystitis; Isolated tissue bath; Metformin; MTT assay